Synthesis of low-cost HNO3-functionalized acetylene black carbon supported Pt-Ru/CAB nano electrocatalysts for the application in direct ethanol fuel cell (DEFC) - Choudhary A.K.; Pramanik H. (My University, 2025)
Ethanol electrooxidation was thoroughly investigated on laboratory synthesized Pt-Ru nano electrocatalysts. Low cost acetylene black carbon functionalized by HNO3 was used as support material for synthesized Pt-Ru/CAB: electrocatalysts. The effect of synthesis methods on the major electrocatalytic properties of Pt-Ru/CAB electrocatalysts were studied thoroughly. The electrocatalysts Pt-Ru/CAB were manufactured by different chemical reduction methods. The electrocatalysts were designated as Pt-Ru/CAB-PLM for polyol reduction and Pt-Ru/CAB-FAM for formic acid reduction method, respectively. The electrocatalyst synthesis method and treatment of support material remarkably enhanced the catalytic performance of synthesized Pt-Ru/CAB electrocatalysts. The commercial Pt-Ru/C was selected as anode electrocatalyst for comparative study with the synthesis electrocatalyst in terms of performance in half cell study and in a single direct ethanol fuel cell as well. In the direct ethanol fuel cell, synthesized Pt-Ru/CAB-PLM produced maximum open circuit voltage of 0.71 V and highest power density of 6.02 mW/cm2 at a current density of 19.52 mA/cm2 at the room temperature of 35 °C. Whereas, the maximum power density of 5.13 mW/cm2 at a current density of 18.70 mA/cm2 and open circuit voltage of 0.717 V were obtained for commercial Pt-Ru/C electrocatalyst at the same temperature (35 °C). The power density enhanced around 2.17 times when cell temperature was increased from 35 °C to 80 °C using anode electrocatalyst Pt-Ru/CAB-PLM. The performance of synthesized Pt-Ru/CAB-PLM is excellent for the ethanol electrooxidation and, thus, could replace commercial Pt-Ru/C. © 2019, The Korean Institute of Chemical Engineers.